The Influence of Leadership Style, Organizational Culture and Supervision on Motivation and Their Impact on Employee Performance at the Regional Financial and Revenue Management Agency of Jambi Province - Hardiansyah Hardiansyah; Pantun Bukit; Osrita Hapsara (DINASTI RESEARCH, 2026)
This study aims to analyze the influence of leadership style, organizational culture, and supervision on work motivation and its impact on employee performance at the Regional Financial and Revenue Management Agency of Jambi Province. This research employs a quantitative approach with independent variables (X) consisting of leadership style, organizational culture, and supervision; an intervening variable (Z) which is work motivation; and a dependent variable (Y) which is employee performance. Data were collected through questionnaires that were previously tested for validity and reliability to ensure the accuracy and consistency of the research instrument. Data analysis techniques include the coefficient of determination (R-Square) to determine the contribution of each variable, the F-test to examine the simultaneous effect, and the t-test to assess the partial effect of each variable. In addition, the Sobel test was applied to analyze the mediating effect of work motivation on the relationship between independent variables and employee performance. The results indicate that leadership style, organizational culture, and supervision have a significant influence on work motivation. Furthermore, work motivation is proven to act as a mediating variable that strengthens the effect of the independent variables on employee performance. Therefore, improving an effective leadership style, a conducive organizational culture, and optimal supervision can enhance work motivation, which in turn positively impacts employee performance at the Regional Financial and Revenue Management Agency of Jambi Province.